Communicating to Drive Sustainability-A Worked Example with Wind Power - Moskowitz, Howard; Thistle, David John; Ortega, George; Aber, Judah; Gere, Attila (Edelweiss Applied Science and Technology, 2020)
We demonstrate the knowledge-development power of the emerging science of Mind Genomics, doing so by a study of appeals to fund a windpower project in Texas. The paper focuses on the method, analyses, results, and application of the findings, showing what can be learned and implemented with the easy-to-do and affordable, iterated studies offered by Mind Genomics. Two groups of respondents evaluated 24 vignettes, comprising different combinations of 16 messages about wind power opportunities and benefits for the State of Texas. The first group of 51 respondents evaluated vignettes about wind-power, rating the vignettes on regarding whether they understood the messages and would recommend what they read. The second group of 50 respondents estimated the unit price of a share of stock based upon the messages in the vignette. The analysis linked the ratings to the presence/absence of each message. Two new-to-the-world mind-sets emerged, those focusing on the benefits to Texas, and those focusing on what specific actions must be taken. The mind-sets suggest different ways that people have of dealing with information in which appeals are embedded. Study 2 reaffirmed these two mind-sets when economic judgments were substituted for opinions. The paper incorporates the PVI, the personal viewpoint identifier, a technology to assign a new person to one of these two mind-sets, thus expanding the scope of the research from a study of a single population to the possible identification of the mind-sets in the general population around the United States or even around the world.